Išuwa towards the end of the XIII century BC (on the problem of the grooved ware) - Aram Kosyan (Banber Arevelagitut'yan Instituti)
At the end of the XIII century BC archaeological excavations carried out in various regions of Eastern Turkey have revealed a complete cultural break, thus marking the end of the Late Bronze Age (LBA) and the rise of the Early Iron Age (EIA). The main peculiarity for the new culture is the appearance of the so-called "grooved ware" which was unearthed during the excavations at numerous sites on the territory of Išuwa, a political unit well attested by Hittite cuneiform texts. This same ware is known also from several sites located in different parts of Eastern Highlands (eastern Lake Van basin, Tillehöyük, Lidarhöyük, Erzurum, Iğdır, etc.). To date the causes of this phenomenon are not clear. Ch. Burney and V. Sevin were the first to assume that at least in the case of the Upper Euphrates basin the transition from LBA to EIA was the result of migration from Transcaucasia. Later this as-sumption was cast doubt on by other archaeologists. U. Müller suggested that the source for the grooved ware should be looked for in Išuwa, and that later some population of this region moved to the south and south-east. For the solution to this problem the author refers to the movement of the population of the Kura-Araxes culture of Transcaucasia and neighboring regions to the south-west and south which happened about 2000 years before the end of the LBA, during the termination of the Early Bronze Age I in Transcaucasia (end of the IV millennium BC). Most probably, the causes of both migrations could be the result of the so-called 5.2 and 3.2 kiloyear climatic events. Strikingly, the routes of the Kura-Araxes I migrants coincide with that of the grooved ware people. Thus, the suggestion of Ch. Burney and V. Sevin seem more plausible than the proposals put forward by later authors. Most probably in both cases we deal with significant migrations of Transcaucasian population groups.